The Variables that Affect Compliance of Muslim Merchants for Zakat Maal in the District of Cianjur - Dadang Husen Sobana; Uus Ahmad Husaeni; Irpan Jamil; Dadang Saepudin (International Journal of Zakat, 2017)
The purpose of this study is to determine the variables that affect the level of compliance among Muslim merchants in the implementation of zakat maal. The quantitative method was used for the investigation and the results were compiled by multiple linear regression analysis. The total population enrolled in this study comprised 100 Muslim merchants. A non-probability sampling technique with this type of sampling was considered suitable for the purpose of this research that the sample collection purpose adapted to the purpose of research. Based on the results of multiple linear regression testing, it can be concluded that compliance zakat maal is affected by the variable level of education, level of income, commitment to Islamic rule, perceptions Zakat justice and transparency of zakat institution. Keywords: Compliance; welfare; Muslim merchants; zakat institution; zakat maal